2003
DOI: 10.1002/pdi.488
|View full text |Cite
|
Sign up to set email alerts
|

Quality of GPs' referral letters to diabetes secondary care

Abstract: Good quality referral information enables appropriate triage and the best use of scarce secondary care resources. We evaluated the quality of GPs' referral letters to our district general hospital diabetes centre to identify types of information that receive the highest and the least priority with the objective of developing constructive feedback.Eighty-one letters from 51 GPs, excluding requests for reassessment, emergency inpatient care or non-diabetic concerns, were evaluated on 24 parameters of varying cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Conscientious GPs were therefore likely to score very high on the referral score, and this could bias the results in favour of the intervention. Nonetheless, the scoring system does equate with referral quality measurement scores used in other referral evaluation studies [ 2 , 5 ]. In addition, further work in this project aimes to assess whether the presence of a greater quantity of relevant clinical information improves the quality of the health care process, and consequently this scoring system seemed appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Conscientious GPs were therefore likely to score very high on the referral score, and this could bias the results in favour of the intervention. Nonetheless, the scoring system does equate with referral quality measurement scores used in other referral evaluation studies [ 2 , 5 ]. In addition, further work in this project aimes to assess whether the presence of a greater quantity of relevant clinical information improves the quality of the health care process, and consequently this scoring system seemed appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nevertheless the quality of referral letters has been and remains variable. [4][5][6][7] In one survey 38% of consultants stated that they have been provided with inadequate information by general practitioners ''fairly'' or ''very often''. 8 Nevertheless, much of the criticism of general practitioners' referral letters has been from a secondary care perspective; it is not clear how well they communicate when measured by their own standards.…”
mentioning
confidence: 99%
“…Change in the completeness of information relayed in a referral request was prespecified as the primary outcome because the main cause of poor quality in referral information is a lack of necessary details. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Additional measures of benefit included change in the accuracy of information relayed and change in the ability to triage the referral request. Measures of potential harm included referring provider satisfaction, which could be negatively impacted if the intervention required increased work by the referring provider, and consultant rated accuracy of triage, which could decrease if the intervention had a negative impact.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Multiple studies have documented that referral requests rarely contain adequate details to allow triaging to occur, 2-4 potentially resulting in delays in scheduling or unnecessary prioritization. Additionally, information vital to the efficiency of the initial consultation, including details of the patient’s history, 2-16 physical examination, 2-8 and laboratory results, 4-6,16,17 infrequently makes it into referral requests. It has been shown that the problem rarely lies with the specialist not knowing what information he or she needs, 3,18,19 but instead with communicating to the referring provider what information is needed.…”
mentioning
confidence: 99%